An statistical quality control study on Mitsukawa Electric Industries, Inc. - Alombro, Kevin; Cardenas, Dorothy F.; Leyble, Edmundo R. (Diliman, Quezon City College of Engineering, 2002)
High quality wires and cables are essential to our country's electric utilities industry. With the country's goal of industrialization and development, power generation becomes the main catalyst. Mitsukawa Electrical Industries, Inc., one of the leaders in wires and cables manufacturing industry, was chosen by the group as the focus of their study in industrial quality control. The group focused its study on the Poly AAC 6/7 wire, which is one of the high-volume products manufactured by the company. Manufacture of this product is divided into three main stages : wire drawing, wire stranding and extrusion. By conducting interviews with the company's plant manager and quality assurance personnel, a Failure Mode Effect and Criticality Analysis was developed for the production process. This, along with other problem-solving tools such as histograms and scatter plots, were used in determining some quality related problems that should be addressed for the chosen product. With the use of problem solving tools, it was established that the company was conducting redundant testing for the wire standing process. Other quality problems that were analyzed were the off-centeredness of drawn wire diameter, failure of drawn wire samples with regards to tensile strength, and failure of the finished product to meet the minimum insulation thickness. Control charts were used in determining whether the processes wherein these attributes were involved were operating in a state of statistical control. Process Capability Indices for these processes were also determined. From the constructed control charts and the calculated process capability indices, it was determined that the wire drawing process was in control and highly capable with regards to product diameter, however, it proved to be incapable for the aspect of tensile strength. The extrusion process was found to be out of control and incapable with regards to the quality characteristic of insulation thickness. The group suggests that it is possible for the company to lower the mean diameter for the wire drawing process without the risk of producing out of specifications. It is also recommended that additional experiments be performed to identify factors that may be causing the other characteristics to be incapable and out of control. The company may also look into the performance of the manufacturing process with regards to other characteristics that were not studied by the group.
Feasibility study
Keywords: Mitsukawa Electric Industries, Incorporated; Electronic industries; Quality control